We are Marshall [videorecording (DVD)] - McG (Joseph McGinty Nichol); McConaughey, Matthew, 1969-; Fox, Matthew, 1966-; Mackie, Anthony, 1978- (Warner Home Video, 2007)
The inspiring story of how a small town in West Virginia, steeped in the rich tradition of college football, struggled to cope with a devastating loss and restore their community after one of the worst disasters in the history of American sports. On the evening of Saturday, November 14, 1970, a chartered jet carrying Marshall University's football team, coaches and fans, was on its way home from a hard-fought game in North Carolina. Less than a minute before its scheduled landing at Tri-State Airport, the plane crashed in the Appalachian Mountains, killing everyone aboard: 37 players, eight coaches and university staff, the flight crew, and 25 prominent Huntington citizens. They find hope and strength in the leadership of outsider Jack Lengyel, a young coach determined to rebuild Marshall's football program. Less than a year after the crash, on September 18, 1971, Marshall University was poised to stage one of the greatest comebacks in collegiate sports.